RETRACTED ARTICLE: Kynurenine promotes neonatal heart regeneration by stimulating cardiomyocyte proliferation and cardiac angiogenesis - Donghong Zhang; Jinfeng Ning; Tharmarajan Ramprasath; Changjiang Yu; Xiaoxu Zheng; Ping Song; Zhonglin Xie; Ming-Hui Zou (Nature Communications, 2022)
Abstract Indoleamine 2,3 dioxygenase-1 (IDO1) catalyzes tryptophan-kynurenine metabolism in many inflammatory and cancer diseases. Of note, acute inflammation that occurs immediately after heart injury is essential for neonatal cardiomyocyte proliferation and heart regeneration. However, the IDO1-catalyzed tryptophan metabolism during heart regeneration is largely unexplored. Here, we find that apical neonatal mouse heart resection surgery led to rapid and consistent increases in cardiac IDO1 expression and kynurenine accumulation. Cardiac deletion of Ido1 gene or chemical inhibition of IDO1 impairs heart regeneration. Mechanistically, elevated kynurenine triggers cardiomyocyte proliferation by activating the cytoplasmic aryl hydrocarbon receptor-SRC-YAP/ERK pathway. In addition, cardiomyocyte-derived kynurenine transports to endothelial cells and stimulates cardiac angiogenesis by promoting aryl hydrocarbon receptor nuclear translocation and enhancing vascular endothelial growth factor A expression. Notably, Ahr deletion prevents indoleamine 2,3 dioxygenase -kynurenine–associated heart regeneration. In summary, increasing indoleamine 2,3 dioxygenase-derived kynurenine level promotes cardiac regeneration by functioning as an endogenous regulator of cardiomyocyte proliferation and cardiac angiogenesis.